2014
DOI: 10.1177/230949901402200224
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Magnetic Resonance Imaging in Thoracic Outlet Syndrome

Abstract: PURPOSE. To evaluate the diagnostic value of magnetic resonance imaging (MRI) in thoracic outlet syndrome (TOS). METHODS. Medical records of 30 women and 10 men aged 18 to 68 (mean, 38) years who presented with unilateral (n=35) and bilateral (n=5) TOS and underwent 42 surgical decompressions of the right (n=23) and left (n=19) sides were reviewed. MRI findings were compared with intra-operative findings to evaluate the diagnostic value of MRI. RESULTS. MRI findings correlated poorly with intra-operative findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 11 publications
(17 reference statements)
0
14
0
12
Order By: Relevance
“…Palpation has highlighted a first rib in elevation and hypertonia of the subclavius and pectoralis minor muscle in the side in dysfunction. These dysfunctions lead to thoracic outlet syndrome, although we did not run specific surveys to diagnose the cause, such as a vascular or neurological compression [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Palpation has highlighted a first rib in elevation and hypertonia of the subclavius and pectoralis minor muscle in the side in dysfunction. These dysfunctions lead to thoracic outlet syndrome, although we did not run specific surveys to diagnose the cause, such as a vascular or neurological compression [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is considered most efficacious for neurogenic TOS, which is often the most difficult form to diagnose. 6 The detailed appreciation of soft tissues on MRI may highlight irritation of the brachial plexus as high signal on T2-weighted sequences. 2 The loss of fat planes surrounding the brachial plexus or close contact with surrounding bone structures is considered pathognomonic of neurogenic TOS.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated poor correlation between MRI and intraoperative findings. The sensitivity and specificity of MRI for diagnosis of TOS in this study was 41% and 33%, respectively [7]. Alternatively, MR Neurography (MRN) shows potential as a beneficial diagnostic tool for nTOS [8].…”
Section: Diagnostic Techniquesmentioning
confidence: 92%